Post- operative Radiotherapy of Conjunctival Malignancies: A Series of 24 Cases - Belaïd, Asma; Nasr, Chiraz; Jmour, Omar; Cherif, Aziz; Kamoun, Hajer; Mahjoubi, Khalil; Abidi, Rim; Yahiaoui, Safia; Zarraa, Semia; Yousfi, Amani; Gargouri, Walid; Bouguila, Hedi; et al. (Asian Pacific Journal of Cancer Biology, 2017)
Objective: To assess the results of post-operative radiation therapy in the management of incompletely resected conjunctival malignancies. Methods: In this retrospective case series, we reviewed the clinical records of all cases of conjunctival tumors treated with post-operative radiotherapy in the radiation oncology department of Salah Azaïz Institute of Tunis, from January 1990 to December 2015. We focused on clinico-pathological characteristics, treatment modalities and patients’ outcome. Results: Twenty four patients were enrolled in our study: 19 men and 5 women. The mean age of our patients was 54 years (range: 20 to 84). The mean basal diameter of the tumor was 11 mm (range 6 to 20 mm). The mean tumor thickness was 4 mm (range 1 to 15 mm). The most frequent histological type was squamous cell carcinoma in 23 cases. One patient had a malignant conjunctival fibrohistiocytoma. Radiation therapy was post-operative for positive or narrow surgical margins in all cases. Eighteen patients were treated with kilovoltage radiation therapy (KVRT). The mean delivered dose to the tumor bed was 64 Gy (range: 60 to 70 Gy). Four patients were treated with an association of KVRT and Strontium 90 plaque brachytherapy. Two patients were treated only with Strontium 90 plaque brachytherapy (2 fractions of 17 Gy). After a median follow-up of 110 months, 19 patients were alive with no evidence of local recurrence in 17 patients. Two patients had a local recurrence and were referred to surgery. Two patients were ost to follow up. The 5-year relapse free survival rate was 90.9%. Radiation-induced side effects were conjunctivitis, cataract, eye watering and glaucoma. Conclusion: Post-operative radiation therapy allows good local control with acceptable toxicities in conjunctival malignancies. Management of these tumors needs a broad collaboration between ophthalmologists and radiation oncologists, to allow a conservative treatment with the lowest rates of local recurrence.